Assessment of Inter-varietal Cross Lines of Gladiolus on Vegetative and Floral Traits for Selection and Promotion in Nepal - Poon, Tul Bahadur; Khanal, Asmita; Timilsina, Sandip; Rijal, Anuja (Nepalese Horticulture, 2021)
Artificial crossing between species and varieties has been effective in producing new gladiolus cultivar with desirable traits. The seeds obtained from the total of twelve inter-varietal cross lines were raised in nurseries in 2013. The corms and cormels were selected yearly from the first phase to the fourth phase of selection. Forty seven inter-varietal cross lines and one check genotype were assessed in preliminary non-replicated trial in 2017 in the field of Regional Agricultural Research Station, Lumle, Nepal. A total of twenty five inter-varietal cross lines of gladiolus was selected, and assessed to develop new productive and attractive varieties of gladiolus on the basis of sixteen traits: the first spike emergence, complete spike emergence, the first floret loosening, maximum number of floret opening at a time, floret diameter, number of florets /spike, days to the seventh floret wilting, flower life, plant height, spike length, rachis length, number of spikes/ mother corm, number of marketable spikes /mother corm, number of filled capsules/spike, number of unfilled capsules/spike and total number of capsules/spike. Forty six inter-varietal cross lines were selectively reduced to twenty five inter-varietal cross lines after they had been assessed in the preliminary trial. Eventually ten cross lines: HRSDG-013-2.17(A), HRSDG-013-7.4(B), HRSDG-013-7.8(A), HRSDG-013-7.8(B), HRSDG-013-8.5(A), HRSDG-013-8.16(A), HRSDG-013-9.12(A-2), HRSDG-013-10.24, HRSDG-013-11.7(B) and HRSDG-013-11.17(B-2) are likely to be promoted for replicated trial so as to develop new desirable varieties in future.